ABILITY FOR SELF-REGULATION AS A CONDITION OF SUCCESSFUL PEDAGOGICAL ACTIVITY - Gagieva, Z.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
The article is devoted to identifying the role of the ability to self-regulation as a condition for the success of professional pedagogical activity in a comprehensive school. In the search for optimal management models and the development of professional and pedagogical activity, the disclosure of the theoretical and procedural foundations for the organization of the educational process in a comprehensive school, the identification of the fundamental characteristics and ways to achieve the professionalism of teachers is of particular importance. The process of increasing the professional competence of specialists in the educational system in modern conditions is determined by a target setting for the development of the psychoemotional qualities of the personality - its motivational, substantive and operational readiness to perform normative functions. Obviously, the success of a teacher's professional activity is largely determined by: firstly, to what extent did they succeed in forming students in the learning process ready for any socially necessary activity, an active desire to participate in common work; secondly, the success of preparing for the performance of professional duties depends on the extent to which future specialists have acquired universal knowledge, which is the basis of any professional activity, in ways that are used in various types of labor activity; thirdly, the success of including students in socially useful work is determined by the level of formation of professionally significant qualities. In this regard, the importance of the formation of students by subjects of educational, quasi-professional and professional activity is being updated even in the process of learning at a university. The subjective position of students during training is the first step and condition for their further active mastery of the complex of types of pedagogical activity. Significant is the awareness of the manifestation of self-regulation, based on knowledge of the characteristics of your personality, theoretical and procedural foundations of regulation of activity.